2002
DOI: 10.1016/s0008-6363(02)00597-7
|View full text |Cite
|
Sign up to set email alerts
|

Host cell-derived cardiomyocytes in sex-mismatch cardiac allografts

Abstract: Our data confirm the existence of mature cardiomyocytes derived from host cells, likely mesenchymal precursors, in the adult cardiac allograft in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…However, this conclusion has been challenged by studies showing lack of transdifferentiation into cardiomyocytes following intracardiac injection of bone marrow cells [3,4] or transfusion of these cells into the circulation of recipient mice [5,6]. Extensive myocardial regeneration from extra-cardiac stem cells in human sexmismatched heart transplants has likewise been described [7], although other studies reported only modest [8] or negligible [9,10] contribution of host-derived cells to cardiomyocytes. Here, we used for the first time an experimental model of heterotopic heart transplantation in rats to investigate engraftment and differentiation of host-derived cells in heart transplants both spontaneously and following administration of granulocyte-colony stimulatory factor (G-CSF) to mobilize bone marrow stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, this conclusion has been challenged by studies showing lack of transdifferentiation into cardiomyocytes following intracardiac injection of bone marrow cells [3,4] or transfusion of these cells into the circulation of recipient mice [5,6]. Extensive myocardial regeneration from extra-cardiac stem cells in human sexmismatched heart transplants has likewise been described [7], although other studies reported only modest [8] or negligible [9,10] contribution of host-derived cells to cardiomyocytes. Here, we used for the first time an experimental model of heterotopic heart transplantation in rats to investigate engraftment and differentiation of host-derived cells in heart transplants both spontaneously and following administration of granulocyte-colony stimulatory factor (G-CSF) to mobilize bone marrow stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…3,9,10 Gender-mismatch heart transplantation has shown the ability of certain host cells, presumably bone marrow-derived mesenchymal stem cells (MSCs), to migrate into the heart. [11][12][13][14][15][16] With this in mind, many investigators have administered intravenously cell preparations containing stem cells to potentially augment the pool of endogenous stem cells homing to the myocardium after infarction. However, the localization of these exogenous cells in the infarcted tissue has relied primarily on postmortem histology, and the dynamic redistribution of peripherally injected stem cells as well as trafficking of cells could only be surmised by comparative studies with serial sacrifice of large numbers of animals.…”
mentioning
confidence: 99%
“…1,2 In humans, the differentiation of progenitor cells into cardiomyocytes has been studied in allografted female hearts transplanted into male recipients by examining the presence of Y-chromosome-positive cells. 3 Diverse results on the magnitude of cardiac chimerism after transplantation have been reported [3][4][5] ; however, the data suggest that adult progenitor cells of non-cardiac origin may translocate from the recipient to the graft.…”
mentioning
confidence: 99%